Body perception and quality of life in ex-volleyball players in Jaén - Torres-Guerrero, Juan; Caracuel-Cáliz, Rafael Francisco; Torres-Campos, Beatriz; Rojas Cepero, Iago; Ramírez-Arrabal, Vicente (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The study analysed the relationship between body image and quality of life of participants in federated volleyball competitions in Jaén. A descriptive and cross-sectional research was carried out, where athletes completed a questionnaire about their body image and quality of life. The captains and coaches completed self-completed surveys. A total of 199 subjects were studied, including 18 captains and 21 coaches. 43.6% of the women and 61.3% of the men considered themselves to have a good quality of life. Participants highlighted the importance of their personal experience in maintaining this lifestyle. In terms of body image perception, men perceived themselves better than women, with 46.9% of men choosing the options "good" or "very good", compared to 41% of women. A direct relationship was found between perceived quality of life and body image, supported by Pearson’s chi-square test using SPSS software, with a value of p= 0,000. The study concludes that athletes, in general, have a high quality of life, with men perceiving it better than women. In addition, male athletes have a better perception of body image than female athletes.